miR-29a-5p Regulates the Proliferation, Invasion, and Migration of Gliomas by Targeting DHRS4 - Dai, Yong; Chen, Zhenhua; Zhao, Wei; Cai, Gang; Wang, Zhifeng; Wang, Xuejiang; Hu, Hongkang; Zhang, Yi (Frontiers in Oncology, 2020)
Gliomas are the most common malignant primary brain tumors in adults and exhibit a spectrum of aberrantly aggressive phenotypes. MicroRNAs (miRNAs) play a regulatory role in various cancers, including gliomas; however, their specific roles and mechanisms have not been fully investigated. Studies have indicated that miR-29a is a tumor-suppressive miRNA, but the data are limited. In this study, we investigated the role of miR-29a-5p in glioma and further explored its underlying mechanisms. On the basis of bioinformatics, dehydrogenase/reductase 4 (DHRS4) was considered a potential target of miR-29a-5p and was also found to be highly expressed in gliomas in our experiments. Moreover, with a luciferase reporter assay, DHRS4 was found to be a target gene of miR-29a-5p and to be correlated with glioma proliferation, invasion, and migration in our in vivo and in vitro experiments. Simultaneously, we observed that the knockdown of DHRS4 rescued the downregulation of glioma proliferation, invasion, and migration caused by treatment with a mir-29a-5p inhibitor. The present findings demonstrate that miR-29a-5p suppresses cell proliferation, invasion, and migration by targeting DHRS4, and DHRS4 may be a potential new oncogene and prognostic factor in gliomas.